2019
DOI: 10.1155/2019/9098256
|View full text |Cite
|
Sign up to set email alerts
|

First Principle Study of the Attachment of Graphene onto Different Terminated Diamond (111) Surfaces

Abstract: The adhesion of a graphene monolayer onto terminated or 2x1-reconstructed diamond (111) surfaces has in the present study been theoretically investigated by using a Density Functional Theory (DFT) method. H, F, O, and OH species were used for the surface termination. The generalized gradient spin density approximation (GG(S)A) with the semiempirical dispersion corrections were used in the study of the Van der Waals interactions. There is a weaker interfacial bond (only of type Wan-der-Waals interaction) at a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Also, the adhesion of a GN monolayer onto a diamond (111) surface with born and nitrogen doping was investigated by first-principle calculations [101,113]. The authors concluded that the GN kept its aromatic character for all terminations and only a moderate charge transfer from the GN to the diamond surface occurs.…”
Section: Friction Tribology and Mechanical Propertiesmentioning
confidence: 99%
“…Also, the adhesion of a GN monolayer onto a diamond (111) surface with born and nitrogen doping was investigated by first-principle calculations [101,113]. The authors concluded that the GN kept its aromatic character for all terminations and only a moderate charge transfer from the GN to the diamond surface occurs.…”
Section: Friction Tribology and Mechanical Propertiesmentioning
confidence: 99%
“…Usually, the electrons within the H-terminated diamond surface are mainly redistributed on the C-H bonds. Nevertheless, electron transfer from the H-terminated diamond surface to the grafted linker and then to ligand is also possible [49].…”
Section: Resultsmentioning
confidence: 99%
“…The electron dispersions, total cohesion energies, and geometrical structures were calculated using DFT employing the generalised gradient approximation (GGA) implemented in the Perdew-Burke-Ernzerhof (PBE) exchange correlation functional [44]. This was done using the Aimpro [45] and Vasp [46] packages to ascertain if any differences manifest when including Van der Waals (VdW) interactions, as this has been suggested to be necessary for the graphene on diamond system [30,31,33].…”
Section: B Computational Detailsmentioning
confidence: 99%
“…The growing demand for miniaturisation has also led to increased interest in the nanoscale properties of diamond [19] and the production of diamond-graphene (sp 3 -sp 2 ) interfaces, investigated both experimentally [20][21][22][23][24][25][26][27][28][29] and through DFT studies [30][31][32][33]. There now exists a multitude of graphene growth systems with the ability to produce high quality epitaxial graphene.…”
Section: Introductionmentioning
confidence: 99%